Penerapan Strategi Pembelajaran Inkuiri Meningkatkan Kemampuan Menganalisis Siswa pada Materi Pertumbuhan & Perkembangan Tumbuhan - Tamara Tamara; Ratna Dewi Munthe; Annisa Aulia Nanda; Namira Yasmine Raudah; Indayana Febriani Tanjung (AS-SABIQUN, 2022)
This study aims to obtain and observe the results of applying Biology learning strategies to students' understanding through the media in the form of LKPD (Student Activity Sheet). The assessment process using an inquiry strategy is carried out using Quasi Experimental (students experiment naturally) in groups. The population object in the application of the inquiry strategy was all students of SMAN 4 Binjai grade 11 IPA 4 again 36 students with 6 research groups on plant growth and development materials. on the differences and comparisons of saplings and mature trees. Data collection techniques used plant samples found in the school environment and guided LKPd filling. by looking at the morphological characteristics of plants and analyzing the differences. The process of observing plants is carried out to see the achievement of students in understanding the material based on the stages of guided inquiry. Based on this students will be able to achieve the learning objectives. The results of the assessment are presented in tabular form to assess critical thinking skills and draw conclusions from the experiments carried out.